Multi-level governance : the missing linkages - Ongaro, Edoardo (Emerald Group Publishing Limited, 2015)
This volume argues that progress in both the study and the practice of Multi-Level Governance may derive from developing linkages with disciplines, perspectives and issues that have so far not been explored in connection to MLG.
Keywords: Decentralization in government -- European Union countries.; Regionalism -- European Union countries.; Central-local government relations -- European Union countries.; Regionalism (International organization); Public administration.; Policy sciences.; European Union countries.; elektronické knihy; electronic books